Influence of endurance training on the recovery of muscle metabolism and power output during repeated sprint exercise - Tsampoukos, A.; Bogdanis, G.; Boobis, L. H.; Nevill, M. E. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Recovery of power output during repeated sprints has been found to be associated with phosphocreatine (PCr) resynthesis and endurance fitness (Bogdanis et al., 1996). The purpose of the present study was to examine whether an improvement of endurance fitness, following endurance training, can hasten power output restoration and PCr resynthesis during repeated bouts of high intensity exercise in female athletes. Fourteen female games players were divided into two groups: training (T; n=9) and control (C; n=5). The T group added endurance training consisting of 30 min running on a level treadmill at 85% of maximal oxygen uptake (VO2 max) 3 times per week, on top of their normal training programme for 6 weeks, while the C group followed their normal training programme. Before and after the 6 weeks training period, all participants performed two 30 s sprints separated by 2 min of passive rest on a non-motorized sprint treadmill. Power output was measured as the product of the horizontally applied force and running speed. Muscle biopsies were taken before and 10 s and 2 min after the first 30 s sprint only in the T group. Adenosine triphosphate (ATP), PCr, glycogen, lactate and glucose-6-phosphate (G6P) were measured in dry muscle. VO2 max and blood lactate responses during submaximal running were also measured before and after training to assess aerobic performance. The percentage of VO2max corresponding to a concentration of 4 mmol/l lactate in the blood (%4mM) was used as an index of endurance fitness. Data were assessed using two-way analyses of variance, paired and independent t-tests. Values are presented as mean±SEM. The additional endurance training resulted in an improvement of %4mM by 8.3±2.8% in the T group, while there was no change in the C group (-1.5±2.5%)(p<0.05). VO2max remained unchanged in both groups. Power output restoration in the second compared with the first sprint was increased more in the T compared with the C group after training (7.4±1.4 vs. 2.1±1.1%, p<0.05). PCr concentration 10 s after the first 30 s sprint was 36.1±11.4% higher (p<0.01) following training in the T group (Table 1), while the rate of glycogen utilization and muscle lactate tended to be lower after training (p=0.054 and p=0.098, respectively; Table 1). In conclusion, this study showed that endurance training improved endurance fitness, and resulted in an enhanced power output restoration during repeated sprint exercise. This may be due to either a greater PCr resynthesis or a greater reliance on aerobic metabolism during sprint exercise.